Analysis of locomotive wheel sets wearing - Mikaliūnas, Šarūnas; Lingaitis, Leonas P.; Subačius, Rimantas (Transport, 2002)
Wearing dynamics of traction rolling-stock wheel tyres of diesel locomotives was investigated. Based on research results it is possible to predict wheel-tyre safety margin, to improve maintenance and state periodicity of repair, as well as to use traction rolling-stock repair funds most efficiently.First Published Online: 19 Oct 2011